Расчет потерь энергии при пробое проводящих сред - Курец В. И. Валерий Исаакович; Филатов Г. П. Геннадий Петрович; Жучков А. И. Александр Иванович; Юшков А. Ю. Анатолий Юрьевич (2003, 2003)
В фонде НТБ ТПУ отсутствует